The Alaska state constitution - McBeath, Gerald A. (Oxford commentaries on the state constitutions of the United States., 2011)
Compared to the constitutional history of the rest of the US, the Constitution of Alaska is in its developmental infancy. However, with the benefit of over 300 years, the Alaskan Constitution is a pioneer and model in - among other things - simplicity, coherence, vision and accessibility. This volume offers a constitutional and historical account of the state's governing charter. In addition to an overview of Alaska's constitutional history, it provides an in-depth analysis of the entire constitution, detailing the many significant changes that have been made since its initial drafting.